THE ANALYSIS OF COST OF ILLNESS OF PREGNANT WOMEN WITH SYPHILIS - A. I. Ovod; M. D. Mukovnina (IRBIS LLC, 2015)
treatment of pregnant women with syphilis, and also members of their families is carried out at the expense of budgetary funds. The economic estimation of expenses for treatment of pregnant women sick of syphilis and members of their families who also take place obligatory inspection and preventive treatment has been spent. Various elements of an expense for the medical and medicinal help are thus calculated.